Growing a growth mindset: characterizing how and why undergraduate students' mindsets change - Lisa B. Limeri; Nathan T. Carter; Jun Choe; Hannah G. Harper; Hannah R. Martin; Annaleigh Benton; Erin L. Dolan (SpringerOpen, 2020)
Abstract Background The extent to which students view their intelligence as improvable (i.e., their "mindset") influences students' thoughts, behaviors, and ultimately their academic success. Thus, understanding the development of students' mindsets is of great interest to education scholars working to understand and promote student success. Recent evidence suggests that students' mindsets continue to develop and change during their first year of college. We built on this work by characterizing how mindsets change and identifying the factors that may be influencing this change among upper-level STEM students. We surveyed 875 students in an organic chemistry course at four points throughout the semester and interviewed a subset of students about their mindsets and academic experiences. Results Latent growth modeling revealed that students tended to shift towards viewing intelligence as a stable trait (i.e., shifted towards a stronger fixed mindset and a weaker growth mindset). This trend was particularly strong for students who persistently struggled in the course. From qualitative analysis of students' written survey responses and interview transcripts, we determined that students attribute their beliefs about intelligence to five factors: academic experiences, observing peers, deducing logically, taking societal cues, and formal learning. Conclusions Extensive prior research has focused on the influence of mindset on academic performance. Our results corroborate this relationship and further suggest that academic performance influences students' mindsets. Thus, our results imply that mindset and academic performance constitute a positive feedback loop. Additionally, we identified factors that influence undergraduates' mindset beliefs, which could be leveraged by researchers and practitioners to design more persuasive and effective mindset interventions to promote student success.